TREN DOMINAN DALAM PENELITIAN ACCOUNTING CONSERVATISM: ANALISIS BIBLIOMETRIK - Kaco, Rahmawati; Rasyid, Syarifuddin; Darmawati, Darmawati (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This research aims to examine the development of research on the topic of accounting conservatism over the last ten years. The data source used is the metadata of articles published on Science Direct between 2013 and 2023. This study uses a literature review search method combining the Open Knowledge Map (OKM) and VOSviewer (VV) applications. The data obtained is processed according to the application procedures used. The results of this study present a mapping and analysis of future research opportunities related to accounting conservatism. OKM is used to map clusters in accounting conservatism, while VV is used to analyze accounting conservatism clusters with different approaches and data sources. Based on the analysis results, the trends shown through VV, namely Stock Price Crash Risk and Corporate Governance, are the topics with the most considerable amount of literature. Based on the two results of the analysis of Earnings Management, Cash Holdings, Accounting Conservatism, Corporate Governance, Audit Committee, and Executive Compensation. The topic of Corporate Governance has extensive research opportunities and needs to continue to be developed.